How to Turn Trust into Non-material Asset of Higher Education - G. Zborovsky; P. Ambarova (Высшее образование в России)
The aim of the article is to consider trust as a basis of University life and non-material asset of higher education development. Based on the materials of the authors’ sociological research, the paper analyzes the problem of trust/distrust in Russian higher education and presents an interpretation of three types of trust in higher education – institutional, community, and moral. The most important functions of trust are characterized. One of them is the development and support of students’ and faculty’s creative motivation. In this case, trust may be converted to intellectual capital of higher education subjects. If the trust level is low, the effectiveness of learning and teaching decreases greatly. Distrust destroys creative and innovative potential of educational communities. Another important function of trust in education is development of partnership and social networks between educational organizations, governing bodies, stakeholders, and parents. Trust has an impact almost on all the spheres of University life but it essentially a non-material asset, therefore, it requires “fine tuning” and fine and careful management. Manifestations of “distrust presumption” of educational management to academic community and an effect of “distrust boomerang “ of educational communities to management are shown. The authors prove that the roots of distrust in higher education are associated with the current system of educational bureaucracy, which imposes a culture of distrust at all levels and in all areas of University life. The conditions and possibilities of turning trust into non-material asset of higher education development are revealed.